Assessment Of Customer Satisfaction With Single Optical Services Using The Servqual Method - Verawati, Ellya (INTERACTION: Jurnal Pendidikan Bahasa, 2024)
Optik Tunggal is a company operating in the eye-related retail sector. Optik Tunggal serves eye refraction, sales of various glasses, sales of contact lenses, and so on related to the eyes. Service is essential because it influences the level of sales in a business. Optik Tunggal continues to strive to make improvements and developments in terms of both products and services. This research aims to determine customer satisfaction with Optik Tunggal services using the service quality method. This service quality method measures the level of satisfaction using five dimensions, namely physical appearance (tangible), reliability, responsiveness, empathy, and assurance. The research was carried out by distributing questionnaires to Optik Tunggal customers who had eye examinations and purchased products in May 2023, totaling 45 respondents, which were then processed using the Service Quality method. The research results show a gap of – 1.19 between the actual service received and customer expectations. The physical appearance dimension has a gap value of -1.05, the reliability dimension -1.19, the responsiveness dimension -1.12, the empathy dimension -1.25, and the assurance dimension -1.36